ANALGESIC EFFECTS OF LIBYAN FRESH POMEGRANATE FRUIT OF PUNICA GRANATUM - بن رابحة, Fatma; حسان, Samia; سعيد, Najat; الأشهب, Mabruka; Kah Hwi, Kim; بن سعيد, Lamees (مجلة العلوم الإنسانية والتطبيقية, 2016)
Context: The severe side effects of analgesic drugs require the search of new analgesics from natural products and nutritional resources known as nutraceutical. Objective: This work aimed to evaluate the analgesic effect of fresh pomegranate Punica granatum fruit juice (fpj) been consumed by Libyans for a century. In this study we investigated the fresh fruit juice given to mice for three subsequent days versus the effect of (fpj) given instantly and those given the ethanol extract of pomegranate Materials and Methods: Antinociceptive activity of fresh pomegranate fruit juice (fpj) was examined using two models of pain. In the writhing test the (fpj) was administered for three subsequent days where no food was given,the (fpj) was also given instantly i.p.(0.15ml/kg) and orally p.o.(0.15ml/kg) for hot tail one group of animals were prefed (fpj) the ethanol pomegranate extract was administered by intraperitoneal route in doses of (100,150 and 200mg/kg) for writhing , hot tail flick test and compared to aspirin 100mg/kg in all tests Results: In the writhing test for mice the index of pain inhibition (IPI) was 47.8% for mice prefed with (fpj) and 37% for ethanol pomegranate extract (200mg/kg i.p.) and 59% for aspirin whereas,the groups treated instantly (0.15ml/10g) i.p.and orally failed to inhibit acetic acid induced writhings. In the hot-tail flick test fresh pomegranate fruit juice (fpj) antinociceptive effect was evident within 15min the maximum possible analgesia ( MPA) was 18% and remained elevated throughout the observation period ethanol pomegranate extract (200mg/kg) showed significant analgesia reaching its peak at 60 min MPA was 24.1% as compared to aspirin 37.5% Conclusion: The results demonstrated that consuming pomegranate fresh fruit leads to significant analgesic activity which may be both peripheral and central.